PENERAPAN GOOGLE MEET DALAM PERKULIAHAN DARING MAHASISWA PGSD PADA MATA KULIAH KONSEP DASAR PKN SD SAAT PANDEMI COVID 19 - Novialita Angga Wiratama (JUSEDA, 2020)
This study aims to describe the application of google meet in online lectures for PGSD students in the Basic Concept of Civics at SD during the COVID-19 pandemic. The subjects of this study were 89 students of PGSD class A and B. This type of research used in this research is descriptive research. Where this research describes the application of google meet in lectures. The method used is a qualitative method which is also called an artistic method, because the research process is more artistic (less patterned) and is also called an interpretive method because the research data is more concerned with the interpretation of the data found in the field. The research data shows that the google meet application in online learning for PGSD students states that it is very easy to access, namely 70 students, while only 2 students experience difficulties. Understanding the material in online lectures using google meet, 25 students stated that they strongly agreed that the material could be understood well. The effectiveness of using the google meet application in online learning 11 students stated that it was very effective while 32 students stated that they did not agree with the effectiveness of learning. Students do not understand the material because sometimes the signal breaks due to cloudy weather or rain. This means that the lecturer provides a solution by always sending the lecture material dictates before the online lecture activity on the WhatsApp group, so that all students can attend lectures without being left behind due to signal constraints. Evaluation of the use of google meet in online lectures after going through 6 meetings, students wishing they could learn using the offline method. According to students, it is easier to understand lecture material if it is done face-to-face without going through the online.